In‐line monitoring of jute fiber–reinforced poly(lactic acid) composite subjected to impact loading using infrared thermography. Issue 48 (15th August 2017) - Boccardi, Simone; Carlomagno, Giovanni Maria; Meola, Carosena; Russo, Pietro; Simeoli, Giorgio
ABSTRACT: Poly(lactic acid) (PLA) is receiving ever more attention from both the academic and the industrial communities because it is green, biobased, and complies well with requirements for work safety and environmental safeguards. However, a question may arise regarding the suitability of PLA in replacing conventional plastics. The response requires a complete material characterization and analysis of its performance in service and its resistance to impact loads. This work is focused on monitoring with infrared thermography the impact damage of a biobased thermoplastic composite, in this case a poly(lactic acid) (PLA) matrix reinforced with jute fibers. The visualization of thermal signatures that develop under impact supplies information useful to understanding the material impact damage mechanisms, such as formation of cracks and their propagation and the overall extension of damage. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45579. Abstract :